Livestock-associated methicillin-resistant Staphylococcus aureus in inpatients: a snapshot from an Italian hospital. (September 2022) - Merla, C.; Kuka, A.; Petazzoni, G.; Postiglione, U.; Zatelli, M.; Gaiarsa, S.; Mariani, B.; Corbella, M.; Marone, P.; Sassera, D.; Cambieri, P.
Highlights: Low prevalence LA-MRSA without clonal expansion. In some cases LA-MRSA were associated with severe infections and bad outcome. LA-MRSA were associated with resistance to several oral antibiotics. Abstract: Objectives: This study aimed to characterize livestock-associated methicillin-resistant Staphylococcus aureus (LA-MRSA) strains isolated from patients admitted to Policlinico San Matteo in Pavia, located in an Italian region with high livestock density. Methods: The starting dataset was composed by 353 MRSA strains isolated from blood cultures between 2011 and 2019 and in 954 MRSA isolated from nasal swabs, wound swabs, skin swabs, ulcer swabs, conjunctival swabs, urine and respiratory samples collected between 2018 and 2019. LA-MRSA was identified based on being MRSA resistant to tetracycline and negative for the PCR amplification of scn locus. Whole genome sequencing of the selected strains was performed, and virulence and resistance genes searched. Results: Five out of 353 MRSA isolates from blood cultures (1.4%) and nine out of 904 MRSA isolates obtained from other materials (1%) were resistant to tetracycline and negative for the scn locus. The 14 strains were also negative for the lukS-pv, tsst, eta and etb loci. Nine of the 14 strains belonged to ST398, the most common ST of LA-MRSA in Europe. ST398 isolates belonged to four spa-types, of which the prevalent was t899. Eight genomes had the cassette SCCmec type V, five genomes had SCCmec type IV and one genome lacked SCCmec, mecA and mecC . Conclusion: The frequency of LA-MRSA in the patients of this study (1.4% in blood cultures, 1% in other samples) is low but relatively constant over time prevalence and comparable to that found in the few studies performed on patients to date.